Modified endoscopic strip craniectomy technique for sagittal craniosynostosis: provides comparable results and avoids bony defects - DAĞÇINAR, ADNAN; SAÇAK, BÜLENT; SAKAR, MUSTAFA; BAYRİ, YAŞAR; ŞAHİN, YENER (SPRINGER, 2022)
Purpose This study describes a modified technique addressing bony defects and incomplete ossification after endoscopic strip craniectomy (ESC) for SC followed by postoperative helmet therapy (PHT). The study aims to delineate quantitative and qualitative outcomes of this modified ESC technique followed by PHT and discern the optimal duration of PHT following ESC. A secondary aim is to address the effects of the technique on bony defects. Methods Patients undergoing ESC followed by PHT between 2017 and 2021 were included. Patient sex, age at surgery, duration of surgery, red blood cell transfusion, length of hospital stay, PHT duration, cephalic index (CI) at multiple time points, and bony defect information were collected. Descriptive and correlative analysis was done. Results Thirty-one patients (25 male, 6 female) were operated in study period. Mean age at surgery was 12.81 weeks, mean duration of surgery was 57.50 min, average transfused RBC volume was 32 cc, mean length of hospital stay was 1.84 days, mean PHT duration was 33.16 weeks, and mean follow-up time was 63.42 weeks. Mean preoperative CI was 70.6, and mean CI at the end of PHT was significantly higher, being 77.1. Maximum improvement in CI (CImax) took place at week 22.97. PHT duration did not have a correlation with CI at last follow up. There were no bony defects. Conclusion Modified ESC technique is effective in successful correction of sagittal craniosynostosis. CImax already takes place, while PHT is continuing, but there is no certain time point for dishelmeting. The technique avoided bony defects and incomplete ossification.
Keywords: Sagittal craniosynostosis; Endoscopic strip craniectomy; Postoperative helmet therapy; Bony defect; Incomplete ossification; PHT duration; TOTAL CALVARIAL RECONSTRUCTION; INTRACRANIAL VOLUME; HELMET THERAPY; MANAGEMENT; OUTCOMES